Projective geometry and spatial reasoning for STEM learning - Thom, Jennifer S.; McGarvey, Lynn M.; Markle, Josh (Frontiers in Education, 2024)
The purpose of this paper was to explore the potential of projective geometry as a supplement or complement to Euclid's geometry in promoting spatial reasoning for STEM learning. Through recovering, updating, and reconceptualizing projective geometry activities within contexts that children find themselves today, we offer the ideas and examples presented here as well as the findings from our larger ongoing studies to inform teaching practices and learning activities in elementary classrooms that can promote children's spatial reasoning for STEM learning through projective geometry.